Ultrasound-Assisted extraction and purification of polysaccharides from Boschniakia rossica: Structural Characterization and antioxidant potential - Minghui Yang; Xingfan Li; Xinyi Du; Falin Li; Tianqi Wang; Yanyan Gao; Jia Liu; Xiongfei Luo; Xiaorui Guo; Zhonghua Tang (Ultrasonics Sonochemistry)
Modern pharmacological investigations have shown that polysaccharides extracted from Boschniakia rossica showcase a range of biological effects. This study identified 260 primary metabolites, with carbohydrate compounds and their derivatives accounting for 80 types. We employed ultrasonic-assisted enzyme extraction (UAEE) to optimize extraction parameters, achieving a crude polysaccharide yield of 13.67%, which is 1.52 times and 1.17 times higher than ultrasonic extraction (UAE) and enzyme extraction (EAE). Additionally, we isolated four distinct purified polysaccharides (BRPS-0, BRPS-1, BRPS-2, BRPS-3), with relative molecular weights of 1569, 2815, and 4572, while BRPS-3 displayed structural complexity. The scanning electron microscope (SEM) revealed that BRPS-0 exhibited distinct crystalline particles, while BRPS-3 displayed an ordered crystal structure. Notably, BRPS-0 demonstrated relatively stable antioxidant activity due to its low molecular weight, high phenolic and sugar content, crystalline microstructure, and abundant α- and β-pyranose configurations, including galacturonic acid, glucose, galactose, and arabinose. This research provides a foundational theory for the comprehensive use of Boschniakia rossica resources and supports its implementation in modern medicine and functional foods.